Pendugaan Karbon Tumbuhan Bawah Di Tegakan Pinus Bumi Perkemahan Pasirbatang Taman Nasional Gunung Ciremai - Yayan Hendrayana; Ika Karyaningsih (Fakultas Biologi Universitas Jenderal Soedirman, 2020)
Plants are a place to store carbon (carbondioxide sink). One way to reduce the impact of global warming is to control carbon concentrations through a sinking program, where organic carbon as a result of photosynthesis will be stored in the biomass of standing forests or woody trees. This study aims to determine the potential amount of biomass and carbon stored in understory at the Pasir Batang Camping Ground, Gunung Ciremai National Park. The method used is the checkered line method, which is placed by purposive sampling. The plots used in this study are 1m x 1m squares which are placed along the path of 30 plots. The results showed that the highest Importance Value Index (IVI) was Canarium callothyrus at 120% and the best was Oxalis corniculata at 3%. The estimated potential of understorey biomass is 92,3 tonnes with an average of 3,08 tonnes/ha. The estimated potential for understorey carbon storage is 43,4 tonnes with an average of 1,45 tonnes/ha.